Comparative Efficacy of Tobacco, Jute and Levavet® Against Gastrointestinal Nematodes in Cattle - Amin, MR; Mostofa, M; Awal, MA; Hakim, SMA (Progressive Agriculture, 2013)
The effect of tobacco (Nicotiana tabacum, Linn., @100mg/kg bwt.), jute (Corchorus capsularis, Linn., @100 mg/kg bwt.) and Levavet® (levamisole, @ 7.5 mg/kg bwt.) against natural gastrointestinal nematodes were studied in cattle. Their effect on hematological parameters (TEC, Hb, PCV and TLC), biochemical parameters (ALT and AST) and clinical parameter (body weight) were also observed. Twenty four (24) naturally parasitized cattle of BAU Dairy Farm, Mymensingh were randomly divided into four groups, each consisting of six (6) cattle. Water extract of leaves of tobacco and jute were administered orally to the cattle of group A and B, respectively. Cattle of group C were treated with Levavet® orally. Cattle of group D was kept as infected control group. Fecal samples, body weight, hematological and biochemical parameters were examined before treatment and on 3rd, 10th, 17th and 28th day. A significant (p<0.01) reduction of EPG count was found following administration of tobacco (34.32-51.26%), jute (8.80-27.76%) and Levavet®(89.31-100%) in cattle. The EPG count of the control group (D) were significantly (p<0.01) increased up to the last day of experimental period. After treatment with tobacco, jute and Levavet®, total erythrocyte count (TEC), hemoglobin (Hb) content and packed cell volume (PCV) were gradually increased significantly (p<0.01 and p<0.05) in cattle. Conversely, the total leukocyte count (TLC) were decreased significantly (p<0.01 and p<0.05) in treated cattle. The alanine aminotransferase (ALT) and aspartate aminotransferase (AST) level were not significantly changed in the cattle. The body weight was increased significantly (p<0.01 and p<0.05) in tobacco, jute and Levavet® treated cattle whereas decreased in control group. It is found that water extracts of tobacco leaves were moderately effective and jute leaves were relatively less effective against mixed gastrointestinal nematode infections in cattle. DOI: http://dx.doi.org/10.3329/pa.v19i1.17108 Progress. Agric. 19(1): 61 - 68, 2008